The impact of blended learning on English language test scores - Orin Karlinda; Raghav Agarwal Srivastava (Early Publishing Group, 2025)
This study explores the impact of blended learning on English language test scores, a crucial area of investigation given the increasing integration of technological tools in language education. As educational institutions adopt hybrid instructional models to enhance engagement, autonomy, and access to authentic language use, understanding their effectiveness in improving test performance is vital for refining pedagogical practices. While previous research indicates positive perceptions and skill development through blended learning, there is a notable research gap concerning specific correlations between blended instruction and formal assessment outcomes. The primary aim of this study is to examine how students perceive the influence of blended learning on their test performance and to identify how engagement with digital components affects their preparation and confidence. Employing an interpretive research design, the study involved 19 undergraduate students enrolled in an English for Academic Purposes (EAP) course at a university in Indonesia. Data were collected through semi-structured face-to-face interviews conducted over four weeks, with recordings transcribed verbatim. Thematic analysis was utilized to interpret the qualitative data, following an inductive approach that involved coding, categorization, and pattern recognition, complemented by peer debriefing and member checking to enhance validity. Key findings reveal that students perceive blended learning as facilitating test familiarity, reducing anxiety, and improving confidence through multimedia content and flexible study options. However, challenges such as overreliance on digital tools and lack of alignment between online materials and actual test demands were also identified. The study underscores the importance of pedagogically guided technology integration and the need for learners to develop self-regulation skills. The findings suggest that, when thoughtfully implemented, blended learning can positively influence English test outcomes, informing educators and curriculum designers to optimize digital integration for improved language assessment performance.